Keikutsertaan Prolanis Berhubungan dengan Kepatuhan Konsumsi Obat Hipertensi - Wilantara, Muhammmad; Mayasari, Ni Made Elva; Zainora, Zainora; Amalia Badri, Putri Rizki (Jurnal Ilmiah Kesehatan, 2025)
Hypertension is one of the chronic diseases with a high incidence rate that can cause serious complications such as stroke and heart failure. PROLANIS (Chronic Disease Management Program) managed by BPJS Kesehatan aims to increase drug consumption compliance in hypertension patients to control blood pressure and prevent complications. This research aims to analyze the relationship between participation in PROLANIS and compliance with the consumption of hypertension drugs at Taman Bacaan Health Center, Palembang. Research design is an observational analytical with a cross-sectional approach. The sample consisted of 94 hypertensive patients who followed PROLANIS, selected using the purposive sampling technique. Data was collected using the Medication Adherence Scale (MMAS-8) questionnaire and analyzed using the Chi-square test. As many as 63.8% of respondents regularly follow PROLANIS, and 57.4% have a high level of compliance in drug consumption. Statistical tests show a significant relationship between the participation of PROLANIS and compliance with the consumption of hypertension drugs (p-value = 0,005). There is a significant relationship between participation in PROLANIS and the level of drug consumption compliance in hypertensive patients. Regular participation in PROLANIS has the potential to increase treatment compliance and prevent hypertension complications.